2021
DOI: 10.1021/acs.chemrestox.0c00463
|View full text |Cite
|
Sign up to set email alerts
|

Base and Nucleotide Excision Repair Pathways in DNA Plasmids Harboring Oxidatively Generated Guanine Lesions

Abstract: The base and nucleotide excision repair pathways (BER and NER, respectively) are two major mechanisms that remove DNA lesions formed by the reactions of genotoxic intermediates with cellular DNA. We have demonstrated earlier that the oxidatively generated guanine lesions spiroiminodihydantoin (Sp) and 5-guanidinohydantoin (Gh) are excised from double-stranded DNA by competing BER and NER in whole-cell extracts [Shafirovich, V., et al. (2016) J. Biol. Chem. 321, 5309− 5319]. In this work we compared the NER and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Subsequent long-term studies on BER and NER processes demonstrated that these repair systems do not work as isolated pathways and that the structure of an oxidative lesion influences the role of NER proteins in the repair response to the oxidative damage. In some cases, both pathways work cooperatively, and NER proteins stimulate the activity of key BER enzymes [1,3,5,[82][83][84][85][86][87][88][89][90][91], but in other cases, the two pathways compete during recognition of the same lesion [92][93][94][95]. The data about XPC function in glycosylase-BER oxidative base lesion sensors-stimulation [96][97][98] raise questions about the relevance of these interactions as far as they absence in XP-C CGs does not lead to neurological disease.…”
Section: Ner Impact In Oxidative Lesions Repairmentioning
confidence: 99%
“…Subsequent long-term studies on BER and NER processes demonstrated that these repair systems do not work as isolated pathways and that the structure of an oxidative lesion influences the role of NER proteins in the repair response to the oxidative damage. In some cases, both pathways work cooperatively, and NER proteins stimulate the activity of key BER enzymes [1,3,5,[82][83][84][85][86][87][88][89][90][91], but in other cases, the two pathways compete during recognition of the same lesion [92][93][94][95]. The data about XPC function in glycosylase-BER oxidative base lesion sensors-stimulation [96][97][98] raise questions about the relevance of these interactions as far as they absence in XP-C CGs does not lead to neurological disease.…”
Section: Ner Impact In Oxidative Lesions Repairmentioning
confidence: 99%
“…The subsequent steps of the full repair mechanism that include the re-synthesis of the gap created by the excision of the damaged oligonucleotides, have not been assessed here because the recognition and excision of the lesions are the key intermediate steps in NER and BER that were of primary interest. Finally, identical, but unmodified oligonucleotides (without lesions) are not incised, and remain intact after incubation in the same cell extracts under identical conditions [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“… 26 , 27 These mutations in DNA are self-repaired by the excision repair mechanism. 28 The UV-B radiations have 1000 times more damaging effects than UV-A. 22 An ever-increasing worldwide utilization of sunblock components has been noticed in the global sun care market of net worth up to 11.6 billion USD in 2018, and it is estimated that it will achieve a globally 24.4 billion USD by 2029.…”
Section: Introductionmentioning
confidence: 99%
“…UV-B radiations are genotoxic radiations that directly cause skin erythema and DNA mutagenic photolesions . The adjacent DNA bases through various molecular rearrangements form dimeric photoproducts such as cyclobutene dimers and pyrimidine (6-4 photoproducts) after direct absorption of UV-B radiations. , These mutations in DNA are self-repaired by the excision repair mechanism . The UV-B radiations have 1000 times more damaging effects than UV-A .…”
Section: Introductionmentioning
confidence: 99%